Interview with the ECM Award winner 2022 and introducing the new ECM members - Son, Kiho (2023)
This article presents the interview with the ERS Early Career Member Awardee 2022 (@MathioudakisAG) and provides a brief introduction to the new ECM members https://bit.ly/3BSRgV2 The Early Career Member (ECM) Award is intended to honour promising members of the European Respiratory Society (ERS) at an early stage of their professional career, based on their curriculum vitae, involvement in the ERS and potential for future scientific contributions. This award is given during the ERS International Congress, where the ECM Awardee is invited to give the Mina Gaga lecture during the ECM session. In this article, we present an interview conducted with the 2022 ECM Award winner, Alexander Mathioudakis, where he discussed his work and visions for the future and shared some tips for ECMs starting a career in respiratory research. We also provide a brief introduction to the new members of the ECM Committee (ECMC) from Assemblies 2 (Respiratory intensive care), 3 (Basic and translational sciences), 7 (Paediatrics) and 8 (Thoracic surgery and transplantation).